Studies on growth and characterization of heterogeneous tungsten oxide nanostructures for photoelectrochemical and gas sensing applications - Senthilkumar, R.; Mahalingam, T.; Ravi, G. (Applied surface science, 2016)
•Synthesis of tungsten oxide nanostructures by tailored thermal evaporation (vapor solid growth) without vacuum and catalyst.•Various morphologies were obtained including nanorods, nanosheet and nanopyramids.•Photo electrochemical properties were studied.•Ethanol gas (10–50ppm) was sensed at room temperature with high response. Tungsten oxide nanostructures were developed on indium tin oxide coated glass substrates by modified thermal evaporation process without using catalyst and vacuum. Depending on the substrate temperature and vapor concentration, different nanostructures like rod, sheet and pyramid were formed. Morphology, phase structure and crystallinity of the nanostructure films were characterized by Scanning electron microscope (SEM), X-ray diffraction (XRD), Raman spectroscopy and HR-TEM. The samples were investigated under dark current and photocurrent and in H2SO4 aqueous solution as a function of applied potential. The saturated photocurrent density of tungsten oxide was found to be ≈14.4μAcm−2. The films were also investigated as resistive gas sensor for ethanol gases (10–50ppm) at room temperature. The response and recovery time were also determined.